2018
DOI: 10.1097/aud.0000000000000565
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Diagnostic Prediction Model for Conductive Conditions in Neonates Using Wideband Acoustic Immittance

Abstract: The developed prediction model accurately discriminated between normal and dysfunctional ears and was well calibrated. The model has potential applications in screening or diagnostic contexts. In a screening context, probabilities could be used to set a referral threshold that is intuitive, easy to apply, and sensitive to the costs associated with true- and false-positive referrals. In a clinical setting, using predicted probabilities in conjunction with graphical displays of WAI could be used for individualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…As part of the routine procedure, audiology practices are gradually moving towards the inclusion of sensitive middle ear measures to improve early identification and timeous intervention of middle ear pathologies. Video otoscopy Lundberg et al 2017;Park et al 2016; and WAI (Kaf 2011;Merchant et al 2021;Myers et al 2018;Shahnaz et al 2009) have demonstrated higher sensitivity in identifying middle ear pathologies. In addition, Keefe et al (2012) reported that WAI can also be used to predict CHL.…”
Section: Scope Of Paraprofessionals Within the Programmatic Approachmentioning
confidence: 99%
“…As part of the routine procedure, audiology practices are gradually moving towards the inclusion of sensitive middle ear measures to improve early identification and timeous intervention of middle ear pathologies. Video otoscopy Lundberg et al 2017;Park et al 2016; and WAI (Kaf 2011;Merchant et al 2021;Myers et al 2018;Shahnaz et al 2009) have demonstrated higher sensitivity in identifying middle ear pathologies. In addition, Keefe et al (2012) reported that WAI can also be used to predict CHL.…”
Section: Scope Of Paraprofessionals Within the Programmatic Approachmentioning
confidence: 99%
“…As part of the routine procedure, audiology practices are gradually moving towards the inclusion of sensitive middle ear measures to improve early identification and timeous intervention of middle ear pathologies. Video otoscopy Lundberg et al 2017;Park et al 2016; and WAI (Kaf 2011;Merchant et al 2021;Myers et al 2018;Shahnaz et al 2009) have demonstrated higher sensitivity in identifying middle ear pathologies. In addition, Keefe et al (2012) reported that WAI can also be used to predict CHL.…”
Section: Scope Of Paraprofessionals Within the Programmatic Approachmentioning
confidence: 99%
“…Feature extraction is the key to the pipeline, and therefore, the existing works regularly focus on it. The common extracted features include interpretable univariate feature [2], interpretable multivariate features [4], abstract multivariate features [20], and abstract CNN-based features [5], where the first two are manually extracted features, the third is obtained by classical machine learning methods such as principal components analysis, and the last is usually based on deep-learning approaches.…”
Section: Classification Of Wbt In Otosclerosismentioning
confidence: 99%
“…The diagrams show different patterns in healthy and otosclerosis middle ears [2,3], but the visual analysis requires professional experience, is time-consuming, and is prone to error. The automatic analysis approaches based on the manual feature extraction often have a limited accuracy and need to be further improved [4,5].…”
Section: Introductionmentioning
confidence: 99%